PENGARUH TAMBAK SILVOFISHERY TERHADAP SIFAT FISIK TANAH MANGROVE SEBAGAI LAHAN KONSERVASI DAERAH MUARA SUNGAI BOGOWONTO KULON PROGO DAERAH ISTIMEWA YOGYAKARTA - Faezatiy, Lulu'Ayu; Mulyanto, Djoko; Nurcholis, Mohammad (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
The Bogowonto River estuary is a coastal area in the open water category because it faces the Indian Ocean directly, it has high wave energy, which will cause erosion and abrasion, and the presence of mangrove and pond ecosystems (silvofishery) can support the development of coastal areas as conservation land. So it is necessary to conduct research to examine the influence of soil physical properties on silvofishing and determine the types of mangroves in the Bogowonto River estuary area. The method used was a survey, where soil samples were tested at the Yogyakarta BPTP Laboratory and the Yogyakarta